EC-Earth A Seamless Earth-System Prediction Approach in Action - Hazeleger, W; Severijns, C; Semmler, T; Stefanescu, S; Yang, S; Wang, X; Wyser, K; Dutra, E; Baldasano, J; Bintanja, R; Bougeault, P; Caballero, R; et al. (2010)
The EC-Earth consortium is a grouping of meteorologists and Earth-system scientists from 10 European countries, put together to face the challenges of climate and weather forecasting. The NWP system of the European Centre for Medium-Range Weather Forecasts (ECWMF) forms the basis of the EC-Earth Earth-system model. NWP models are designed to accurately capture short-term atmospheric fluctuations. They are used for forecasts at daily-to-seasonal time scales and include data assimilation capabilities. Climate models are designed to represent the global coupled ocean-atmosphere system. The atmospheric model of EC-Earth version 2, is based on ECMWF's Integrated Forecasting System (IFS), cycle 31R1, corresponding to the current seasonal forecast system of ECMWF. The EC-Earth consortium and ECMWF are collaborating on development of initialization procedures to improve long-term predictions. The EC-Earth model displays good performance from daily up to inter-annual time scales and for long-term mean climate.